Phonological errors of selected ijebu undergraduate french learners in two southwestern universities in Nigeria (2011)
This essay examined the typology of errors and what factors are responsible for the errors in the spoken French of Ijebu undergraduate French learners in two Southwestern Universities, Nigeria. It also reports the findings of a pilot study carried out on this study. The major elicitation instrument is the Labovian sociolinguistic interview which is supplemented by reading materials (Labov 1966). The theoretical framework that was used in the analysis of data was interference theory. In the end, the study concluded that the teaching of phonetics and phonology of French language should be emphasized especially in the Anglophone setting for better mastery of speech production of French sounds and words.